Comparing vaccination coverage before and during COVID-19 pandemic in children under one year in the health district of commune V in Bamako, Mali - Mountaga Diallo; Ilo Dicko; Samou Dembélé; Brahima Konaté; Cheick Oumar Doumbia; Ibrahim Sanogo; Ousmane Boua Togola; Drissa Konaté; Moussa Sangaré; Hawa Thiam; Yaya Ibrahim Coulibaly; Sory Ibrahim Diawara; et al. (BMC, 2023)
Abstract Introduction Although an essential frontline service in the prevention of child morbidity and mortality, there are indications that routine vaccinations have been disrupted during the COVID-19 pandemic. The present study aimed to compare vaccination coverage before COVID-19 in Mali in 2019 and during COVID-19 in 2020. Objective To compare vaccination coverages before COVID-19 in Mali in 2019 and during COVID-19 in 2020. Design Cross-sectional study. Setting and participants We collected routine immunization data from 2019 to 2020 of children under one year in the health district of Commune V in Bamako which includes twelve community health centers (CSCom). Results Considering all vaccines together, coverage in 2019 was higher than in 2020 (88.7% vs. 71,6%) (p < 10− 3, Fig. 1). In 2020, low proportions of children vaccinated were observed in May (51.1%) two months after the first COVID-19 case in Mali on March 25, 2020. For all vaccines, the mean number of children vaccinated was significantly higher in 2019 (before COVID-19) as compared to 2020 (during COVID-19) (p < 0.05). However, in September and October 2019 BCG vaccine coverage was lower in 2019 as compared to 2020 (p < 10− 3). Conclusion COVID-19 pandemic has affected routine childhood vaccine coverage in Commune V of Bamako, particularly in May 2020. Therefore, new strategies are needed to improve vaccine coverage in young children below 1.